2020
DOI: 10.1016/j.jsv.2020.115256
|View full text |Cite
|
Sign up to set email alerts
|

On the structural dynamics of laminated composite plates and sandwich structures; a new perspective on damping identification

Abstract: This paper presents the modelling and the dynamic characterization of laminated composite plates and sandwich structures in terms of stiffness and damping. The developments used in this paper are based on the analytical multilayer model of Guyader and Lesueur (JSV, 1978). The model considers linear shear, membrane and bending effects in each layer. The characteristics of the structure are determined by means of an equivalent thin plate methodology. The first main novelty of this paper consists in adapting this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Guyader and Cacciolati [16] later adapted the previous model of Guyader and Lesueur to identify equivalent properties of isotropic multilayers. Note that this work has been recently extended to anisotropic multilayers [17]. Ege et al [18] compared the equivalent models of RKU and Guyader with the Lamb waves model and observed consistent results in terms of equivalent stiffnesses and slightly different damping loss factors.…”
Section: Introductionmentioning
confidence: 66%
“…Guyader and Cacciolati [16] later adapted the previous model of Guyader and Lesueur to identify equivalent properties of isotropic multilayers. Note that this work has been recently extended to anisotropic multilayers [17]. Ege et al [18] compared the equivalent models of RKU and Guyader with the Lamb waves model and observed consistent results in terms of equivalent stiffnesses and slightly different damping loss factors.…”
Section: Introductionmentioning
confidence: 66%
“…Three different equivalent plate characteristics (anisotropic, orthotropic or elliptical orthotropic) have been assumed as well. Note that a similar equivalent methodology has already been studied with this analytical model for the anisotropic case on carbon fiber composite plates [21].…”
Section: Equivalent Analytical Modelmentioning
confidence: 99%
“…The increasing demand for stable performance in harsh environments such as vibration and noise has led to the noise control problem of PGR exterior body to the forefront [18][19][20]. The results showed that the vibration of the EBS, sound field and damping coupling interface affected the noise in the PGR [21]. The vibration of the EBS produces noise, which in turn produces an additional response to the EBS because of the sound pressure [22][23][24].…”
Section: Introductionmentioning
confidence: 99%